Detection and Quantitation of Gluten in Fermented-Hydrolyzed Foods by Antibody-Based Methods: Challenges, Progress, and a Potential Path Forward - Panda, Rakhi; Garber, Eric A. E. (Frontiers in Nutrition, 2019)
Celiac disease (CD) affects approximately 1 in 141 individuals in the United States, requiring adherence to a strict gluten-free diet. The Codex Standard and the European Commission states that gluten level of gluten-free foods must not exceed 20 ppm. The FDA requires food bearing the labeling claim “gluten-free” to contain less than 20 ppm gluten. Accurate quantitation of gluten in fermented-hydrolyzed food is a challenge due to the lack of appropriate reference materials and variable proteolysis. The recent uses of proteases (e.g. proline endopeptidases or PEP) to hydrolyze immunopathogenic sequences of gluten proteins further complicates the quantitation of immunopathogenic gluten. The commercially available methods routinely used to detect and quantitate gluten are not able to distinguish between different hydrolytic patterns arising from differences in fermentation processes. This is a severe limitation that makes accurate quantitation and, ultimately, a detailed evaluation of any potential health risk associated with consuming the food difficult. With an aim to ensure accurate quantitation of gluten in fermented-hydrolyzed foods by taking into consideration the diversity of the peptide profiles generated during the fermentation process, a novel multiplex-competitive ELISA method was recently developed. The ELISA utilizes the G12, R5, 2D4, MIoBS, and Skerritt antibody-HRP conjugates employed in nine commercial gluten ELISA methods and simultaneously measures gliadin, deamidated gliadin, and glutenin specific epitopes. Western blot analysis provided added information into the antigenic targets being detected by the multiplex-competitive ELISA. Together, the multiplex-competitive ELISA and western blot analysis provide insight into the extent of proteolysis resulting from various fermentation processes and have the potential to aid in the selection of appropriate hydrolytic calibration standards, leading to accurate gluten quantitation in fermented-hydrolyzed foods.